2017
DOI: 10.1186/s12906-017-1972-0
|View full text |Cite
|
Sign up to set email alerts
|

Bidens pilosa Ethylene acetate extract can protect against L-NAME-induced hypertension on rats

Abstract: BackgroundEssential hypertension is mainly caused by endothelial dysfunction which results from nitric oxide (NO) deficiency. The present study was design to evaluate the protective effect of Bidens pilosa ethylene acetate extract (Bp) on L-NAME induced hypertension and oxidative stress in rats.MethodsMale Wistar rats were used to induce hypertension by the administration of L-NAME (a non-pecific nitric oxide inhibitor) (50 mg/kg/day). The others groups were receiving concomitantly L-NAME plus Bp extract (75 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
7
28
0
1
Order By: Relevance
“…Ethanol treated rats showed a significant decrease in HDL-cholesterol and increase in total cholesterol, triglycerides, and LDL-cholesterol levels as well as the atherogenic index. These findings are in agreement with results obtained by some authors who reported that hypercholesterolemia and dyslipidemia are associated with the pathogenesis of hypertension induced by chronic ethanol and sucrose intake or L-NAME [20, 21]. According to Stevens et al [22], dyslipidemia is a major risk factor for atherosclerosis that promotes increased vascular resistance and contributes to increased blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…Ethanol treated rats showed a significant decrease in HDL-cholesterol and increase in total cholesterol, triglycerides, and LDL-cholesterol levels as well as the atherogenic index. These findings are in agreement with results obtained by some authors who reported that hypercholesterolemia and dyslipidemia are associated with the pathogenesis of hypertension induced by chronic ethanol and sucrose intake or L-NAME [20, 21]. According to Stevens et al [22], dyslipidemia is a major risk factor for atherosclerosis that promotes increased vascular resistance and contributes to increased blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, animals receiving simultaneous administration of L-NAME and HSCE showed lower systolic blood pressure as compared with animals receiving only L-NAME. Similar data were reported for Nitraria sibirica (Senejouxa et al, 2012), Bidens pilosa (Bilanda et al, 2017), Ulmus wallichiana (Syeda et al, 2016), Antidesma thwaitesianum (Kukongviriyapan et al, 2015), plants with NO-mediated hypotensive effect. The in vitro studies using the MVB preparation pre-contracted by Phen also support that the vasorelaxant mechanism of lythrine is likely to be mediated by activation of NO release from vascular endothelium, since the removal of endothelial cells led to absence of the response to HSCE.…”
Section: Discussionsupporting
confidence: 86%
“…Bidens pilosa L. ( B. pilosa ) is a cosmopolitan weed occurring mostly in hot tropical areas including sub-Saharan Africa, where it is a widely consumed leafy green vegetable source [ 1 , 2 ]. This plant is not only recognized for its nutritional value, but also for its pharmacological and bio-medical importance [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%